Influence of Early Age on the Wave Velocity and Dynamic Compressive Strength of Concrete Based on Split Hopkinson Pressure Bar Tests - Shiming Wang; Longjun Dong; Jian Zhou (Shock and Vibration)
The effect of early age on the mechanical properties of concrete was investigated in this study. A uniaxial compression test was performed on split Hopkinson pressure bar (SHPB) equipment with a large diameter of 75 mm. The experimental results indicated that before 7 days, concrete showed viscoelasticity and had good deformation ability and low sensitivity to incident energy. In addition, the concrete exhibited the characteristics of quasi-brittle materials, and the sensitivity of the incident energy improved with age. The threshold value of the incident energy at early ages had an insignificant effect on the stable age concrete. The threshold value was 50% of the corresponding age’s critical incident energy, while it was 75% after 7 days.